Analysis of English Language Empowerment in Foreign Tourist Services to Improve the Economy of Kawah Ijen Trolley Workers in Banyuwangi - DONI HADI IRAWAN (Jurnal Edukasi, 2025)
Kawah Ijen in Banyuwangi, East Java, is one of Indonesia’s most prominent natural attractions, known for its sulfur crater and the world-famous blue fire phenomenon. Beyond its geological significance, the area illustrates a unique socio-economic transformation in which local sulfur miners have transitioned into tourism service providers, particularly as trolley operators transporting tourists to the crater rim. This study explores the interplay between natural resources, community adaptation, and the role of English proficiency in supporting sustainable tourism. Data were collected through literature reviews, tourism statistics, and expert perspectives. The findings reveal that while tourism provides greater economic opportunities compared to sulfur mining, communication barriers, especially with foreign tourists, pose significant challenges. English language training and community-based capacity building are crucial for enhancing service quality, tourist satisfaction, and long-term sustainability of Kawah Ijen as a world-class destination.